The reduced mobility of the population of Palócföld: Accessibility proposal for better traffic in the Ipoly Valley - Feketéné Benkó, Kata (Studia Mundi – Economica, 2023)
The territories and borders of European countries changed a lot during the last century, which had a positive effect on some states and a negative effect on others, but in all cases it can be said that it led to a reorganizati-on of territorial processes. In addition to the loss of territory, Hungary does not have a border region where the new state border would not have divided a naturally formed region in two. The borders, among other things, by eliminating transport options, turned the border areas into "backwaters", which led to devaluation.The purpose of the research is to prove that a specific aspect of value creation is the creation of cross-border transport, including the realization of transport accessible to everyone by creating the availability of public transport services. The purpose of cross-border transport is to improve the situation of two peripheral regions that exist side by side, but are unable to cooperate on a permanent basis due to the lack of transport connecti-ons. The first stage of linkages is the existence of infrastructure on which certain activities can be carried out, such as individual modes of transport, organized group transport and freight transport. However, the existence of public transport or public transport services occupies a prominent place in the development of regions. During the research, in addition to the state of the infrastructure, different public transport services were mapped and compared, and the value-creating power of public transport services was verified by comparing social and eco-nomic phenomena